Variasi Leksikon sebagai Penanda Status Sosial dalam Komunikasi Adat Masyarakat Wabula, Sulawesi Tenggara - Istiqamah Idrus Sere; Muhammad Suryadi (Universitas Muhammadiyah Surakarta, 2026)
This study aims to describe the lexical variation of Wabula Community in Southeast Sulawesi as amarker of social status in their traditional communication. This research is motivated by the limitednumber of studies that specifically examine the relationship between the choice of traditional lexiconand the social hierarchical structure in Wabula community interactions. We use a qualitative descriptivemethod with data collection through observation and interviews with traditional leaders, religiousfigures, and local communities. Data are analyzed by identifying lexicon that appears in speech andexamining its social function based on the speaker's intention adjusted to the context. This analysis usesLabov's theory on language variation and social strata, which views power relations and social statusas phenomena that influence language. In Wabula traditional practices, the choice of lexical formsfunctions as a social marker that indicates status, respect, and role in the traditional hierarchy. Theresults show that lexicons such as tabea, mande, and amanto, which are used for parabhela, imam, andthe general public, respectively, have different social functions. This variation confirms that languageserves as a marker of hierarchy, politeness, identity, and social relations in Wabula society.